Variation in Prescription Opioid Dispensing across Neighborhoods of Diverse Socioeconomic Disadvantages in Victoria, Australia - M Mofizul Islam; Dennis Wollersheim (MDPI AG, 2018)
The study examined the relationship between dispensing patterns of prescription opioids, neighborhood-disadvantage-index, and standardized doses dispensed. Three-year’s dispensing data drawn from 80 local government areas (LGAs) within Victoria, Australia’s second most populous state, was analyzed. Quantities dispensed in defined daily dose (DDD)/1000-people/day were computed for LGAs of low, moderate, high, and very high socio-economic disadvantage. LGAs with various levels of dispensing, and neighborhood disadvantage were identified and mapped. A multivariable regression model examined the effect of neighborhood level disadvantage and identified other factors that are associated with standardized doses dispensed. More women were dispensed opioids than men. Dispensing increased with increasing age. Most of the LGAs with relatively high dispensing were socioeconomically disadvantaged and located outside the major cities. Dispensing gradually increased from low disadvantage to very high disadvantage areas. Dispensing of standardized doses were consistently higher in rural areas than in urban areas. Neighborhood level disadvantage, age, sex, and urbanization were significant factors in the standardized doses dispensed. As inappropriate dispensing of opioids is a major public health problem, research should facilitate understanding of utilization in small areas to enable tailored public health programs. Nationwide and consistent introduction of real-time prescription drug-monitoring programs, and structural interventions to reduce the fundamental causes of socioeconomic disadvantage and isolation are recommended.